Influence of cluster composition on the diffusion and convective mechanisms limit in gaseous mixtures - Kossov, V.N.; Moldabekova, M.S.; Fedorenko, O.V. (Recent Contributions to Physics, 2013)
Study of the influence of cluster composition in binary gas mixtures Ar-He and Ar-N2 on the transition boundary between the stable diffusion and the concentration gravitation convection is carried out. Binary mixtures argon-helium and argon-nitrogen are considered as three-component systems Ar-(Ar)2-Не and Ar-(Ar)2-N2. Cluster composition of the heavy component Ar is calculated on the basis of virial state equation analysis at the different temperatures and pressures. System Ar-He is investigated in the temperature range (301.0 – 353.0) K in the circular cross-section cylindrical channel. Pressure researches in the range (0.298 – 1.074) MPa are conducted for the system Ar-N2 in the flat vertical channel. Finding indicates that the increase of critical Rayleigh numbers determining the transition from the stable state to the unstable one is observed with increasing dimmer concentration of Ar.